Sociocultural, resilience, persistence and gender role expectation factors that contribute to the academic success of Hispanic females - Parra, Marcela Ortega (Kansas State University, 2007)
The purpose of this qualitative collective case study was to examine the sociocultural and gender role expectation factors that contributed to the success of 10 Latina/Hispanic female high school graduates now attending a large university in the Midwest. Additionally, the study investigated the characteristics of resilience and persistence that helped these women continue their pursuit of higher education in spite of the challenges they faced. The participants in this study were identified as recent immigrants from Mexico or Mexican-Americans born in the United States of Mexican immigrant parents. All of these respondents graduated from a midwestern K-12 public school system and are now attending a large Midwestern university. This study used a qualitative paradigm and open-ended, in-depth interviews for data collection. The 17 question interview focused on the areas of sociocultural backgrounds, resilience/persistence factors, and gender role expectations. Demographic data about the participants’ life histories and educational experiences were collected during the 90-minute interviews. Findings in the study indicated that Latinas are faced with many conflicts. They have specific gender role expectations placed on them and are limited by cultural rules and norms. Along with these conflicts they learn to build resilience/persistence attributes to help them succeed in their academic careers. The seven factors that contributed to the lived experiences and factors of resilience/persistence of Latina/Hispanic female academic success included: 1) lived discrimination; 2) the need to obtain an education that would lead to a better life; 3) active involvement in extracurricular activities in school; 4) strict and protective parents; 5) positive role models from family and other Latinas; 6) traumatic life experiences; 7) and strong familial/parental support. Additionally, the study also revealed six more contributing factors to the sociocultural and gender role expectations and pressures that impact the success of Latina/Hispanic female students in a K-12 public school system. Those factors included traditional Hispanic households, living in two worlds, traditional gender role expectations, independence from family, transference of parental gender role expectations, and the behavioral expectations for Latinas. The study offers recommendations for future studies and implications for practice advising and encouraging Hispanic females to pursue their academic goals.
Keywords: Hispanic females; Resilience; Gender roles; Academic Success; Culture; Sociocultural; Education, Curriculum and Instruction (0727)